Muntingia calabura: chemical composition, bioactive component and traditional uses - Mastuki, Siti Nurulhuda; Mohd Faudzi, Siti Munirah; Ismail, Norsharina; Saad, Norazalina (Springer, 2019)
Muntingia calabura, commonly known as Jamaican cherry, is a plant species belonging to the family Muntingiaceae with variety of traditional uses. Following on these folklore claims, the works on phytochemicals constituents, traditional uses, pharmacological benefits and their mechanisms are presented in a number of studies as well as the in vitro and in vivo investigations. This species contains valuable phytochemicals with known medicinal properties that are beneficial to the well-being (e.g. anti-microbial, anti-nociceptive, anti-inflammatory etc.). Still, further and in-depth researches including a well-designed pharmacological tests and randomized clinical trials are required to unlock the hidden potential medicinal values of this plant, thus lead to the new drug discoveries of M. calabura.